Toward a Cashless Society. Cash and Non-Cash Payments in Spain, 1989-2014 - Maixé-Altés, J. Carles; Mourelle, Estefanía (Panoeconomicus, 2023)
This work investigates the relationships between the retail payment system, monetary aggregates and economic activity in Spain from a long-run perspective. This approach is considered from the perspective of the transformations favored by ICT in the payment system, which incorporates increasingly more and more cashless instruments. The methodology used is based on cointegration analysis and error correction models. Likewise, a new indicator of some trends in the implementation of cashless transactions in payment systems is proposed; this measure has been applied to Spain and other European countries. With respect to long-run relationships, we demonstrate the relevant (and direct) impact of changes in the monetary system and national income on the value of cashless transactions. Regarding the short run, the most important relationships in terms of the value of cashless transactions are those related to the real estate sector. The empirical results evidence the intensive progress of the cashless society in Spain, where the banking sector, regulatory changes and ICT development have played a key role. JEL: E42; E51; G20.